Code Switching and Code Mixing In Bilingualism Community in Pekon Balak Village, Wonosobo District, and Tanggamus Regency: Sociolinguistic Study - Japri, Japri; Dedi, Fransisca S.O.; Maryova R, Frieska (CV. Tripe Konsultan, 2022)
This study aims to describe the form of code-switching and code-mixing, to describe the background of the occurrence of code-switching and code-mixing, and to describe the function of code-switching and code-mixing in a bilingual society in Pekon Balak village, Wonosobo district, Tanggamus district. The research method used is the listening method with the basic techniques of tapping techniques and advanced techniques of listening to engaging in conversation and free listening to engaging in conversation, recording techniques and note-taking techniques are also used in this study. The findings in this study show that code-switching is dominated by code-switching from Javanese Banten to Lampung language, while code-mixing is dominated by code mixing in the form of word insertion. The background to the occurrence of code-switching is dominated by the subject of the conversation, while the background to the occurrence of code-mixing is dominated by the relationship between a language and the topic being discussed. The code-switching function is dominated by the interaction function, while the function dominates the code-mixing function to show one's identity